THE EFFECTS OF A BASKETBALL SCHOOL PROGRAM ON SOME MOTOR AND SITUATIONAL-MOTOR ABILITIES OF CHILDREN AGED 12-14 YEARS - Alem Kukić; Muhedin Hodžić; Faris Rašidagić; Ferhat Nožinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In order to determine quantitative changes that occur under the influence of basketball school program on children, and under the influence of motor and situationalmotor abilities, results obtained on a sample of 65 subjects are analyzed. The applied program from the basketball school gave a statistically significant quantitative changes for basic motor abilities variables, as well as for variables for assesment of situational-motor abilities.